Thermal annealing effects on La2Hf2O7:Eu3+ nanoparticles: a curious case study of structural evolution and site-specific photo- and radio-luminescence. Issue 10 (31st August 2018) - Gupta, Santosh K.; Zuniga, Jose P.; Abdou, Maya; Mao, Yuanbing
Abstract : High temperature annealed La2 Hf2 O7 :Eu 3+ nanoparticles favor tunneling of Eu 3+ to symmetric sites showing orange emission, whereas low temperature annealed samples favor red emission. Abstract : Thermal annealing has a profound effect on material characteristics such as defects, crystallinity, surface area, size, morphology, etc ., and is followed by significant influence on their optoelectronic and scintillator properties. As a function of annealing temperature, our as-synthesized La2 Hf2 O7 :Eu 3+ NPs, by a molten-salt method (MSS), showed a systematic increase in quantum efficiency and emission output up to 950 °C before a slight reduction at 1050 °C. This phenomenon has been attributed to the decrease of surface defects as a function of annealing temperature. In addition, the asymmetry ratio decreases monotonically as a function of annealing temperature and a completely symmetric environment around europium was observed at 1050 °C. This can be correlated with the fact that the crystal structure becomes more and more ordered (ideal pyrochlore) as the annealing temperature is increased. The sample annealed at 1050 °C displayed site-specific luminescence and can be useful in designing need based orange or red phosphors. The synthesized materials show different emission characteristics in terms of asymmetry and emission output under excitation with highly energetic X-ray beams. The current work highlights the importance of thermal treatment in modulating the light emitting properties of red phosphors and X-ray scintillators.